Expectativas Racionales, Equilibrio Perpetuo y Desempleo Involuntario - Noriega Ureña, Fernando Antonio (2006)
The aim of this paper is to show -in sharp contrast to the traditional results of the new classical economics- that rational expectations of economic agents in an environment characterized by full price flexibility are completely compatible with involuntary unemployment. The results here exhibited show a strong convergence to those that belong to the theory of nonexistence of labor market: in it the labor sector is not a market that would clear up through real wages adjustment; labor demand becomes a positive function of real wages, not a negative function as suggested by neoclassical tradition, and involuntary unemployment coexists with perpetual equilibrium in the product market. It is also shown that the use of nominal wages as a resource for inflation control has as an unavoidable counterpart in the growth of unemployment. For it we follow the rational expectation method suggested by Lucas in some of his seminal works, method that has been generally accepted along the discipline.